The Japan Geriatrics Society consensus statement "recommendations for older persons to receive the best medical and long‐term care during the COVID‐19 outbreak—considering the timing of advance care planning implementation". Issue 12 (2nd November 2020) - ,; Kuzuya, Masafumi; Aita, Kaoruko; Katayama, Yoko; Katsuya, Tomohiro; Nishikawa, Mitsunori; Hirahara, Satoshi; Miura, Hisayuki; Yanagawa, Madoka; Arai, Hidenori; Iijima, Katsuya; Okochi, Jiro; et al.
Abstract : Since the end of 2019, a life‐threatening infectious disease (coronavirus disease 2019: COVID‐19) has spread globally, and numerous victims have been reported. In particular, older persons tend to suffer more severely when infected with a novel coronavirus (SARS‐CoV‐2) and have higher case mortality rates; additionally, outbreaks frequently occur in hospitals and long‐term care facilities where most of the residents are older persons. Unfortunately, it has been stated that the COVID‐19 pandemic has caused a medical collapse in some countries, resulting in the depletion of medical resources, such as ventilators, and triage based on chronological age. Furthermore, as some COVID‐19 cases show a rapid deterioration of clinical symptoms and accordingly, the medical and long‐term care staff cannot always confirm the patient's values and wishes in time, we are very concerned as to whether older patients are receiving the medical and long‐term care services that they wish for. It was once again recognized that it is vital to implement advance care planning as early as possible before suffering from COVID‐19. To this end, in August 2020, the Japan Geriatrics Society announced ethical recommendations for medical and long‐term care for older persons and emphasized the importance of conducting advance care planning at earlier stages. Geriatr Gerontol Int 2020; 20: 1112–1119 .